Perception of Genital Cancer among Women attending the OPD of Tertiary Care Hospital in Old part of Dhaka City - Sultana, Nasreen; Begum, Hosne Ara; Nahar, Najmun; Jesmin, Asma; Ara, Ismat; Mallick, Hasina Emroz; Tasnim, Anika (Journal of Dhaka National Medical College & Hospital, 2012)
Genital cancer is increasing day by day in Bangladesh. Among those cervical cancer is the most common constituting about 22-29% throughout the country. Breast cancer is the second most common cause and it is about 13-17% of the female cancer. In Bangladesh, risk factors for cervical cancer are related to early marriage, early sexual activities, multiparity, STD,s and low socioeconomic condition. Lack of knowledge about the risk factors is also an important determinant behind the incidence of these cancers. With the objectives to assess whether they can mention the name of female genital cancer and risk factors for those cancers, this study was conducted. Methodology: This was a prospective observational study. Total 297 women attending the outpatient department of obstetrics and Gynaecology Unit of Dhaka National Medical College Hospital were interviewed with a preset questionnaire during a period of January to March 2009.Results: About 85.8% of women could mention that they had heard of genital cancers. Among those they mentioned the name of uterus (65%), cervix (5.5%) and breast (29.5%). None of them could mention ovarian or other genital cancers. Among them only 19.2% mentioned the risk factors. Risk factors they mentioned were genital infection (15.79%), OCP (21.93%), multiple sexual partners (10.53%), white discharge (21.93%), repeated MR (12.28%), many children in early age (8.77%), no breast feeding (8.77%). They heard of cancer from various sources such as media (43.14%), relative (30.20%), doctors and other service providers (18.80%), patients (5.90%) and book (1.96%).This study found that majority of women know about the genital cancer and all of them were eager to learn more about genital cancers and their prevention. Cervical and breast cancer screening program is started in Bangladesh. There is also media campaign. Awareness development, supervised screening set up and monitoring can reduce the preventable genital cancers in our country. DOI: http://dx.doi.org/10.3329/jdnmch.v17i1.12183 J. Dhaka National Med. Coll. Hos. 2011; 17 (01): 4-7